Corrosion resistance verification method of TC4 material

By strictly controlling the testing medium and sample treatment, precise setting of the test environment and angle, and combining multiple evaluation methods, the problems of high precision and low error in the corrosion resistance verification of TC4 materials are solved, and efficient and reliable corrosion resistance verification is achieved.

CN119666711APending Publication Date: 2025-03-21JIANGSU TIANGONG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411819220.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has high precision and low error optimization space in the verification of corrosion resistance performance of TC4 materials, especially in salt spray tests.

Method used

The stability of the test conditions is ensured by strictly controlling the preparation parameters of the test media, such as the relative density and pH value of the sodium chloride solution. At the same time, a standardized sample cleaning, drying and inspection process is designed, the sample placement angle and spacing are accurately set, the environmental parameters of the test chamber are regulated, and the results are evaluated using a variety of evaluation methods.

Benefits of technology

It realizes efficient and reliable verification of the corrosion resistance of TC4 materials, reduces test errors, improves the accuracy and scientificity of the results, and adapts to the verification needs of samples with different shapes and sizes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a TC4 material corrosion resistance verification method. The method comprises the following steps of test medium preparation, sample preparation, sample placement, salt spray test parameter setting, test process monitoring and test result evaluation. A sodium chloride solution with the relative density of 1.029-1.036 is prepared at the temperature of 25 DEG C, and the pH value of the solution is adjusted, so that the stability of a test medium is ensured; a TC4 sample with a standard size is adopted, and the surface is subjected to cleaning, drying and microscopic examination, so that the quality of the sample is ensured; placing the sample in a salt spray test box according to an angle of 15-25 degrees, setting temperature, humidity, spray pressure and time parameters, and accurately controlling a test environment; the corrosion behavior of the sample is scientifically evaluated by combining a rating judgment method, a weighing judgment method and a corrosive appearance judgment method. The method can effectively improve the accuracy and repeatability of TC4 material corrosion resistance verification, is suitable for the fields of aviation, aerospace, ocean engineering, medical instruments and the like, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a material performance testing and verification method, and more specifically to a TC4 material corrosion resistance verification method. Background Art

[0002] TC4 material is a typical titanium alloy, which has been widely used in aerospace, marine engineering, medical equipment and other fields due to its excellent mechanical properties, low density and excellent corrosion resistance. However, since TC4 material is exposed to corrosive environments such as marine environments, high humidity areas or certain chemical conditions, the verification of its corrosion resistance has become a key link in product quality control.

[0003] The most commonly used corrosion resistance evaluation method is the salt spray test. The salt spray test is an artificial accelerated corrosion test that simulates the corrosion factors in the natural environment to quickly evaluate the corrosion resistance of materials or coatings. The salt spray test is widely used in the corrosion resistance verification of metal materials and surface treatment processes because of its simple operation and intuitive effect.

[0004] Regarding the verification of the corrosion resistance of TC4 materials, although the existing technology covers all aspects of the test process, there is still room for optimization for high-precision, low-error salt spray test solutions. Summary of the invention

[0005] In order to solve the shortcomings of the existing technology, a method for verifying the corrosion resistance of TC4 material is provided. The specific scheme is as follows:

[0006] A method for verifying the corrosion resistance of TC4 material, the verification method comprising the following steps:

[0007] S1. Preparation of the test medium: prepare sodium chloride solution at 25°C; the purity of the sodium chloride used is ≥99.5%, the water used for dissolution is distilled water or deionized water, and the conductivity is ≤2μS / cm; adjust the pH value of the solution according to the test type; after preparation, filter the solution through a filter membrane with a pore size of 0.45μm;

[0008] S2. Sample preparation: Prepare standard TC4 alloy samples; use anhydrous ethanol to clean the sample surface to remove grease and dirt, then rinse with deionized water, and then use hot air to dry at 50±5℃;

[0009] S3. Placement of samples: Fix the samples on the rack of the salt spray test chamber, with the samples at an angle of 15° to 25° to the vertical direction; keep the distance between the samples ≥ 20mm, and the distance from the test chamber wall ≥ 50mm; ensure that the surface of the samples is evenly exposed to the salt spray;

[0010] S4. Set salt spray test parameters;

[0011] S5. Test process monitoring: Use a sedimentation plate to measure the salt spray deposition every day to ensure that it is within 1-2mL / 80cm 2 h; test the pH value and concentration of the test solution daily, and adjust and replace the solution when necessary; keep the test box sealed to avoid external contamination;

[0012] S6. Test result evaluation: Use any one of the following methods to evaluate the test result: the rating method, the weighing method, and the corrosion product appearance method;

[0013] S7. Processing after the test is completed: After the test is completed, take out the sample, rinse the residual salt spray on the surface with deionized water and dry it for storage; record all parameter data of the test process, including environmental conditions, corrosion level, mass loss and microscopic observation images.

[0014] Furthermore, the relative density of the sodium chloride solution in S1 is controlled within the range of 1.029 to 1.036.

[0015] Furthermore, the pH value in S1 is adjusted to 6.5 to 7.2 for the solution in the neutral salt spray test, and 3.1 to 3.3 for the solution in the acetic acid salt spray test.

[0016] Furthermore, the size of the standard flat specimen in S2 is 100mm×50mm×2mm, and the number of specimens is not less than 3.

[0017] Furthermore, in S3, the specimen is 20° from the vertical direction.

[0018] Furthermore, the grading method in S6 is: based on the ratio of the corrosion area to the total area of ​​the sample surface, the grade standard is 0 for no corrosion, 1 for slight corrosion, and 2 for moderate corrosion; the weighing method is to use a high-precision balance with an accuracy of 0.1 mg to weigh and calculate the mass loss of the sample. If the mass loss Δm≤0.5 mg / cm 2 , it is judged as qualified; the method for judging the presence of corrosion products is to observe whether there is corrosion on the surface of the sample. If there is no obvious rust, spots or peeling, it is judged as qualified.

[0019] Furthermore, the salt spray test parameters in S4 are neutral salt spray test at 35±2℃ or acetic acid salt spray test at 50±2℃, and the relative humidity is maintained at ≥95%; the nozzle pressure is set to 0.07-0.17MPa, and the salt spray deposition is 1-2mL / 80cm 2 h; Set the test time according to the test purpose. The short-term evaluation is 24 hours, and the long-term evaluation is more than 72 hours.

[0020] Furthermore, in S2, an optical microscope is used to inspect the surface of the sample to ensure that there are no scratches, contaminants or defects.

[0021] Beneficial effects:

[0022] The present invention provides an improved method for verifying the corrosion resistance of TC4 material, which has the following beneficial effects:

[0023] ① By strictly controlling the preparation parameters of the test medium, including the relative density of the sodium chloride solution, pH value and filtration process, the test errors caused by fluctuations in solution concentration or interference from impurities are effectively avoided, ensuring the stability of the test conditions and the reliability of the results. A standardized sample cleaning, drying and inspection process is designed based on the characteristics of TC4 materials, which can eliminate the interference of surface contamination and human factors on the test, and at the same time adapt to the preparation needs of samples of different shapes and sizes.

[0024] ② By accurately setting the sample placement angle and spacing, the uniformity of salt spray deposition is ensured to avoid excessive local corrosion or insufficient corrosion in blind areas.

[0025] ③ By precisely controlling key parameters such as test chamber temperature, humidity, spray pressure and spray time, a variety of complex corrosion environments are simulated, which helps to comprehensively evaluate the corrosion resistance of TC4 materials in actual use scenarios.

[0026] ④ The present invention provides a variety of evaluation methods such as rating determination method, weighing determination method and corrosion product appearance determination method, and combines microscopic analysis means to quantify and qualitatively evaluate corrosion characteristics, adapt to different verification needs, and improve the accuracy and scientificity of the evaluation. DETAILED DESCRIPTION

[0027] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0028] The present invention provides an improved method for verifying the corrosion resistance of TC4 material, aiming to improve the accuracy and repeatability of the verification method by optimizing test steps, strictly controlling parameters and scientifically evaluating results.

[0029] This embodiment includes the following steps:

[0030] 1. Preparation of test medium

[0031] 1.1 Solution preparation

[0032] At 25°C, prepare sodium chloride solution.

[0033] Relative density of the solution: 1.029-1.036, use sodium chloride that meets the purity requirements (purity ≥99.5%).

[0034] Dissolving water: distilled water or deionized water, conductivity ≤ 2μS / cm.

[0035] 1.2 pH adjustment

[0036] Adjust the pH of the solution according to the type of test:

[0037] Neutral salt spray test: The pH value of the solution is controlled at 6.5-7.2 (25±2℃).

[0038] Acetic acid salt spray test: The pH value of the solution is controlled at 3.1-3.3 (25±2℃) and adjusted by adding appropriate amount of glacial acetic acid.

[0039] 1.3 Filtration

[0040] After preparation and pH adjustment, the solution was filtered through a 0.45 μm filter membrane to remove solid impurities and ensure the purity of the solution.

[0041] 2. Sample Preparation

[0042] 2.1 Sample specifications

[0043] Material: TC4 alloy (conforms to ASTM B265 standard).

[0044] Size: Standard flat specimen, size is 100mm×50mm×2mm, or adjusted according to test requirements.

[0045] Quantity: At least 3 parallel specimens to ensure repeatability.

[0046] 2.2 Surface cleaning

[0047] Method: Use anhydrous ethanol to clean the sample surface to remove grease and dirt, and then rinse with deionized water.

[0048] Drying: Use a hot air dryer with the temperature set at 50±5℃ to avoid moisture residue.

[0049] 2.3 Surface inspection

[0050] Tools: optical microscope (magnification ≥ 100 times).

[0051] Requirements: Ensure that the surface has no visible scratches, contaminants or defects.

[0052] 3. Sample placement

[0053] 3.1 Placement angle

[0054] Fix the sample on the rack of the salt spray test chamber:

[0055] It forms an angle of 15° to 25° with the vertical direction, and the preferred angle is 20°.

[0056] Ensure that the surface of the sample is evenly exposed to the salt spray, but avoid direct spray.

[0057] 3.2 Prevent contact

[0058] Between samples: spacing ≥ 20 mm.

[0059] With the box: The specimen should be kept at a distance of ≥50mm from the wall of the test box.

[0060] 4. Salt spray test parameter setting

[0061] 4.1 Test environment control

[0062] Temperature: The temperature in the test chamber is controlled at 35±2℃ (neutral salt spray test) or 50±2℃ (acetic acid salt spray test).

[0063] Relative humidity: Humidity inside the box ≥95%.

[0064] Salt spray precipitation: 1~2mL / 80cm 2 ·h.

[0065] 4.2 Spray settings

[0066] Nozzle pressure: controlled at 0.07~0.17MPa.

[0067] Spray interval: According to the test requirements, use continuous spray or periodic spray.

[0068] Spray uniformity: Through the sedimentation plate test, ensure that the sedimentation distribution is uniform.

[0069] 4.3 Test cycle

[0070] Set the salt spray exposure time according to the test purpose:

[0071] Short-term assessment: 24 hours.

[0072] Long-term evaluation: 72 hours or longer, the specific time is determined according to the corrosion resistance requirements.

[0073] 5. Test process monitoring

[0074] 5.1 Settlement inspection

[0075] Use a sedimentation plate to measure the salt spray deposition regularly every day to ensure that it meets the requirements of 1-2mL / 80cm 2 The range of h.

[0076] 5.2 Solution inspection

[0077] Check the pH and concentration of the test solution daily and adjust and replace it when necessary.

[0078] 5.3 Pollution Control

[0079] Make sure the test chamber is well sealed to prevent the entry of external dust or contaminants.

[0080] 6. Evaluation of test results

[0081] 6.1 Rating determination method

[0082] The ratio of the corrosion area to the total area of ​​the sample surface is graded, and the judgment criteria are as follows:

[0083] Level 0: No corrosion.

[0084] Level 1: Slight corrosion, corrosion area ≤5%.

[0085] Level 2: Moderate corrosion, the corrosion area is between 5% and 15%.

[0086] 6.2 Weighing determination method

[0087] Use a high-precision balance (accuracy 0.1 mg) to weigh before and after the test and calculate the mass loss Δm:

[0088] Δm=m 初 -m 末

[0089] If the mass loss Δm≤0.5mg / cm 2 , it is judged as qualified.

[0090] 6.3 Method for determining the presence of corrosion products

[0091] Observe the surface of the sample for obvious corrosion (such as rust, spots or peeling).

[0092] No corrosive substances: qualified.

[0093] Presence of corrosive products: Failure.

[0094] 7. Post-test processing

[0095] 7.1 Sample storage

[0096] After the test, take out the sample and rinse the residual salt spray on the surface with deionized water to avoid secondary corrosion.

[0097] 7.2 Data Recording

[0098] Record all data during the test, including:

[0099] Environmental parameters (temperature, humidity, pH value, etc.).

[0100] Corrosion grade or mass loss data.

[0101] Sample surface image (micrograph).

[0102] Through the detection and verification method of the above embodiment, the present invention can realize efficient and reliable verification of the corrosion resistance of TC4 material, meet the needs of refined evaluation, and provide a scientific basis for material application.

[0103] As a further improvement, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for verifying the corrosion resistance of TC4 material, characterized in that: The verification method comprises the following steps: S1. Preparation of the test medium: prepare sodium chloride solution at 25°C; the dissolving water is distilled water or deionized water, and the conductivity is ≤2μS / cm; adjust the solution pH value according to the test type; after preparation, filter the solution through a filter membrane with a pore size of 0.45μm; S2. Sample preparation: Prepare standard TC4 alloy samples; use anhydrous ethanol to clean the sample surface to remove grease and dirt, then rinse with deionized water, and then use hot air to dry at 50±5℃; S3. Placement of samples: Fix the samples on the rack of the salt spray test chamber, with the samples at an angle of 15° to 25° to the vertical direction; keep the distance between the samples ≥ 20mm and the distance from the test chamber wall ≥ 50mm; S4. Set salt spray test parameters; S5. Test process monitoring: Use a sedimentation plate to measure the salt spray deposition every day to ensure that it is within 1-2mL / 80cm 2 h range; test the pH value and concentration of the test solution daily; S6. Test result evaluation: Use any one of the following methods to evaluate the test result: the rating method, the weighing method, and the corrosion product appearance method; S7. Processing after the test is completed: After the test is completed, take out the sample, rinse the residual salt spray on the surface with deionized water and dry it for storage; record all parameter data of the test process, including environmental conditions, corrosion level, mass loss and microscopic observation images.

2. A method for verifying the corrosion resistance of TC4 material according to claim 1, characterized in that: The relative density of the sodium chloride solution in S1 is controlled at 1.029-1.

036.

3. A method for verifying the corrosion resistance of TC4 material according to claim 1, characterized in that: The pH value in S1 was adjusted to 6.5 to 7.2 for the solution in the neutral salt spray test and 3.1 to 3.3 for the solution in the acetic acid salt spray test.

4. A method for verifying the corrosion resistance of TC4 material according to claim 1, characterized in that: The size of the standard flat specimen in S2 is 100mm×50mm×2mm, and the number of specimens shall not be less than 3.

5. A method for verifying the corrosion resistance of TC4 material according to claim 1, characterized in that: In S3, the specimen is 20° from the vertical.

6. A method for verifying the corrosion resistance of TC4 material according to claim 1, characterized in that: The grading method in S6 is: based on the ratio of the corrosion area to the total area of ​​the sample surface, the grade standard is 0 for no corrosion, 1 for slight corrosion, and 2 for moderate corrosion; the weighing method is to use a high-precision balance with an accuracy of 0.1mg to weigh and calculate the mass loss of the sample. If the mass loss Δm≤0.5mg / cm 2 , it is judged as qualified; the method for judging the presence of corrosion products is to observe whether there is corrosion on the surface of the sample. If there is no obvious rust, spots or peeling, it is judged as qualified.

7. A method for verifying the corrosion resistance of TC4 material according to claim 1, characterized in that: The salt spray test parameters in S4 are neutral salt spray test at 35±2℃ or acetic acid salt spray test at 50±2℃, and the relative humidity is maintained at ≥95%; the nozzle pressure is set to 0.07~0.17MPa, and the salt spray deposition is 1~2mL / 80cm 2 h; Set the test time according to the test purpose. The short-term evaluation is 24 hours, and the long-term evaluation is more than 72 hours.

8. A method for verifying the corrosion resistance of TC4 material according to claim 1, characterized in that: In S2, the sample surface is inspected using an optical microscope to ensure there are no scratches, contaminants or defects.